Meningkatkan Hasil Belajar Passing Bawah Permainan Bola Voli Melalui Model Pembelajaran TGT - Buka, Riski Darma; Ruslan, Ruslan; Ilham, Al (-, 2025)
Based on the results of research on the learning outcomes of lower passing in volleyball games through the TGT (Teams Games Tournament) type learning model in class XI TKJ 1 SMK N 2 Limboto, it is concluded that the TGT (Teams Games Tournament) type learning model can improve students' lower passing skills. Based on the initial data results of learning volleyball lower passing skills, students in class XI TKJ 1 SMK N 1 Limboto obtained an average score of 38.70. The results of observations of students who took the low pass rate performance test in cycle I showed that the average score was 56.24. The increase in the average score and percentage of the classification of lower passing skills in cycle II reached 87.12. These results certainly confirm the success of learning lower passing skills using the TGT (Teams Games Tournament) type learning model.